Degradation Behavior of Concrete after Freeze-Thaw Cycles and Then Exposure to High Temperatures - Qifang Xie; Liujie Yang; Fangzheng Hu; Wenming Hao; Shenghua Yin; Lipeng Zhang (Advances in Materials Science and Engineering)
Concrete behavior usually degrades due to freeze-thaw cycles, fire, or both. Existing studies on the degradation behavior of concrete due to exposure to high temperatures were primarily focused on unfrozen concrete. In this paper, the degradation behavior of damaged concrete, after different freeze-thaw cycles (25, 35, 45, and 55 cycles), exposure temperatures (20°C, 300°C, 400°C, and 500°C), and cooling methods (water-cooled and air-cooled), was tested with seventy-five prism specimens. The degradation behavior of the damaged concrete, such as surface characteristics, weight loss, compressive strength, peak strains, and elastic modulus, was studied and analyzed. Results show that (i) the surface color of the concrete does not change significantly throughout the test. As the number of freeze-thaw cycles and temperatures increase, the weight loss of the concrete specimens increases gradually. (ii) After freeze-thaw cycles, the relative strengths and elastic modulus of the concrete specimens significantly degrade compared with those of the unfrozen ones at same temperatures. (c) At elevated number of freeze-thaw cycles and exposure temperatures, the peak strain of the concrete increases gradually. (d) Cooling methods have different effects on the degradation of concrete under different number of freeze-thaw cycles. Finally, a uniaxial compression constitutive model for concrete after freeze-thaw cycles and then exposure to high temperatures was established and a good agreement was observed with test results.